Vortex‐assisted liquid–liquid micro‐extraction and high‐performance liquid chromatography for a higher sensitivity methyl methacrylate determination in biological matrices. (21st November 2013) - Sousa, Tiago F. A.; Aniceto, Marta C.; Amorim, Célia G.; Souto‐Lopes, Mariana; Pérez‐Mongiovi, Daniel; Montenegro, Maria C. B. S. M.; Araújo, Alberto N.
ABSTRACT A vortex‐assisted liquid–liquid micro‐extraction coupled with high‐performance liquid chromatography, with UV–vis, is proposed to pre‐concentrate methyl methacrylate and to improve separation in biological matrices. The use of 1‐octanol as extracting phase, its volume, the need for a dispersant agent, the agitation conditions and the cooling time before phase separation were evaluated. In optimum conditions, enrichment factors of 20 (±0.5) and enrichment recovery of 99% were obtained. The straightforward association of this extraction process with the HPLC method, previously regulated by the International Organization for Standardization, afforded a detection limit of 122 ng/mL and a quantification limit of 370 ng/mL. The within‐batch precision, relative standard deviation, was 3% for a sample with 1.49 µg/mL and 4% for a sample with 13.4 µg/mL. The results showed a between batch‐precision of 21% for experiments performed on five different days, for a sample with a concentration of 1.10 µg/mL in methyl methacrylate. Copyright © 2013 John Wiley & Sons, Ltd.